Free energy calculations on the stability of the 14-3-3ζ protein - Jandova, Zuzana; Trosanova, Zuzana; Weisova, Veronika; Oostenbrink, Chris; Hritz, Jozef (Biochimica et biophysica acta. Proteins and proteomics, 2018)
Mutations of cysteine are often introduced to e.g. avoid formation of non-physiological inter-molecular disulfide bridges in in-vitro experiments, or to maintain specificity in labeling experiments. Alanine or serine is typically preferred, which usually do not alter the overall protein stability, when the original cysteine was surface exposed. However, selecting the optimal mutation for cysteines in the hydrophobic core of the protein is more challenging. In this work, the stability of selected Cys mutants of 14-3-3ζ was predicted by free-energy calculations and the obtained data were compared with experimentally determined stabilities. Both the computational predictions as well as the experimental validation point at a significant destabilization of mutants C94A and C94S. This destabilization could be attributed to the formation of hydrophobic cavities and a polar solvation of a hydrophilic side chain. A L12E, M78K double mutant was further studied in terms of its reduced dimerization propensity. In contrast to naïve expectations, this double mutant did not lead to the formation of strong salt bridges, which was rationalized in terms of a preferred solvation of the ionic species. Again, experiments agreed with the calculations by confirming the monomerization of the double mutants. Overall, the simulation data is in good agreement with experiments and offers additional insight into the stability and dimerization of this important family of regulatory proteins.
Keywords: mutace; 14-3-3 Proteins; cystein; proteiny 14-3-3; Kinetics; stabilita proteinů; počítačová simulace; Protein Stability; lidé; Mutation; Protein Multimerization; Computer Simulation; Models, Molecular; Humans; Protein Conformation; molekulární modely; Cysteine; Thermodynamics; konformace proteinů; multimerizace proteinu; termodynamika; kinetika; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions